Resource Recovery from Waste, Water and Wastewaters with Membrane Technologies - Koyuncu, Ismail; Zeytuncu, Bihter; Pasaoglu, Mehmet Emin; Yuksekdag, Ayse; Kose-Mutlu, Borte (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
In this study, critical elements (Boron (B) and Rare Earth Elements (REE)) recovery is studied with membrane technologies. Concentrated boron can be recovered by using different technologies. Membrane technologies such as reverse osmosis have a potential to concentrate the boron. pH of the solution is very important if reverse osmosis is applied. Removal of boron at pH levels of 7 and 10 increases from 80% to 97% with reverse osmosis membranes. Another critical element is rare earth elements in the World. Rare earth elements (REE) is a group of elements that involve lanthanides, scandium and yttrium. A successful REE transport for wastewater was observed compared with the concentrate flow of the acidic waste slime.